1991
DOI: 10.1097/00000658-199106000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Fracture from Major Blunt Trauma Outcome Is Determined by Associated Injuries

Abstract: Pelvic hemorrhage has been implicated as the cause of death in 50% of patients who die following pelvic fractures. To establish correlates of morbidity and mortality from pelvic fractures due to blunt trauma, we reviewed 236 patients treated during 4 years. The average age of the 144 men and 92 women was 31.5 years, the average Injury Severity Score was 21.3, the average blood requirement was 5 units, and the average hospital stay was 16.8 days. One hundred fifty-two patients (64.4%) were injured in motor vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
85
1
8

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(105 citation statements)
references
References 21 publications
7
85
1
8
Order By: Relevance
“…We identified the most frequent causes and time points of death in patients with pelvic ring fractures who did not survive. The mortality rate of our study population was 4%, lower than mortality rates reported by most previous studies [1, 5,6,14,15,20,21,25,27,35,36,38]. This reduction of mortality might be explained by constant progresses in the early treatment of pelvic ring injuries, including immediate mechanical stabilization of the pelvic ring and improved bleeding control techniques, but also by progresses in intensive care medicine and emergency management of multiple traumas [17,46].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…We identified the most frequent causes and time points of death in patients with pelvic ring fractures who did not survive. The mortality rate of our study population was 4%, lower than mortality rates reported by most previous studies [1, 5,6,14,15,20,21,25,27,35,36,38]. This reduction of mortality might be explained by constant progresses in the early treatment of pelvic ring injuries, including immediate mechanical stabilization of the pelvic ring and improved bleeding control techniques, but also by progresses in intensive care medicine and emergency management of multiple traumas [17,46].…”
Section: Discussioncontrasting
confidence: 54%
“…However, in a substantial number of cases, mortality was not caused by the pelvic injury alone, but by a combination of multiple injuries to different body regions, including the pelvis. While brain injuries were consistently reported as a main reason for mortality in pelvic fracture patients, data from the literature on the incidence of lethal pelvic bleeding were conflicting [21,23,25,27,35,36]. This heterogeneity of data might have been due to the fact that isolated pelvic fractures were rarely lethal injuries, but a combination of pelvic and abdominal or thoracic bleeding often took a fatal course.…”
Section: Discussionmentioning
confidence: 99%
“…About 75% of all pelvic injuries occur in men [6] [7] [8] [9] [10]. The incidence of pelvic fracture resulting from blunt trauma increases with obese patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic ring fractures in young individuals are most commonly caused by high-energy trauma such as falls from a height or traffic accidents [20,21]. In the elderly, however, low-energy impacts often lead to fractures of the pelvic ring [4,21].…”
Section: Introductionmentioning
confidence: 99%